2006
DOI: 10.1128/jvi.00098-06
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Elk and Deer Prions to Transgenic Mice

Abstract: Chronic wasting disease (CWD) is a fatal prion disease in deer and elk. Unique among the prion diseases, it is transmitted among captive and free-ranging animals. To facilitate studies of the biology of CWD prions, we generated five lines of transgenic (Tg) mice expressing prion protein (PrP) from Rocky Mountain elk (Cervus elaphus nelsoni), denoted Tg(ElkPrP), and two lines of Tg mice expressing PrP common to white-tailed deer (Odocoileus virginianus) and mule deer (Odocoileus hemionus), denoted Tg(DePrP). No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(186 citation statements)
references
References 56 publications
(80 reference statements)
13
170
3
Order By: Relevance
“…Whereas the elk PrP expressing mice developed disease after only 118-142 days post-inoculation, human PrP expressing mice (129M) did not develop any features of TSE after more than 657 or more than 756 days [41]. In accordance with these results, Tamgüney et al also reported that human PrP overexpressing mice were not susceptible to nine CWD isolates from mule deer, white-tailed deer, and elk [84]. However, mice have a limited lifespan and further passages may be necessary to detect low levels of prion pinfectivity that may be present subclinically.…”
Section: Human Susceptibility To Cwdmentioning
confidence: 64%
See 2 more Smart Citations
“…Whereas the elk PrP expressing mice developed disease after only 118-142 days post-inoculation, human PrP expressing mice (129M) did not develop any features of TSE after more than 657 or more than 756 days [41]. In accordance with these results, Tamgüney et al also reported that human PrP overexpressing mice were not susceptible to nine CWD isolates from mule deer, white-tailed deer, and elk [84]. However, mice have a limited lifespan and further passages may be necessary to detect low levels of prion pinfectivity that may be present subclinically.…”
Section: Human Susceptibility To Cwdmentioning
confidence: 64%
“…Several transgenic mice expressing cervid PrP have since been produced using different constructs and sequences [10,41,44,52,84] (detailed in Tab. I).…”
Section: Tools For Cwd Research: Cell Lines and Cervid Prp Expressingmentioning
confidence: 99%
See 1 more Smart Citation
“…This apparent lack of species barrier after homotypic transmission -i.e. when the host expresses a PrP gene identical to that of the infecting species -has led to the development of a long list of mice transgenic for sheep [60,197,203], bovine [20,41,48,175], human [5,22,113,190], cervid [30,82,113,117,134,188] and mink [206] PrP. Most of such lines were obtained by additional transgenesis, and have an endogenous PrP null (PrP 0/0 ) background, in order to avoid any interfering effect of the resident murine PrP gene [39,190].…”
Section: Influence Of the Prp Genementioning
confidence: 99%
“…Two other 'absolute' species barriers in mice have recently been broken. Expression of mink PrP [206] and cervid PrP [30,82,113,117,134,188] in transgenic mice render them susceptible to TME and CWD, respectively. It is noteworthy that the use of transgenic mice overexpressing mouse PrP C also allowed the propagation of the CWD agent [179].…”
Section: 'Absolute' Species Barriermentioning
confidence: 99%